2018
DOI: 10.1002/ecy.2406
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effects of soil type on assemblage size and structure in a diverse herbivore community

Abstract: Soil type is understudied as a driver of herbivore community size and structure across host plants. This study extends predictions of resource availability hypotheses to understand how soil types of different resource levels alter plant resistance and structure of herbivore assemblages. In this 2-yr study we use seven dominant chaparral shrub species that grow across a natural mosaic of low and high resource soils to explore effects of soil type on plant resistance, and relate these soil-based differences in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…We study these linkages in a system of woody chaparral shrubs, with their associated lepidopteran herbivores, which grow across a mosaic of low-resource serpentine and higher-resource nonserpentine soils. Prior work in this system has found that plant resistance varies with soil type in a manner consistent with resource availability theory (23). Our goal is to understand how natural variation in abiotic resources might shape network modularity, and to parse the mechanistic basis of such differences between evolutionary (fundamental) and ecological (realized) trophic characteristics of species.…”
Section: Significancementioning
confidence: 63%
See 1 more Smart Citation
“…We study these linkages in a system of woody chaparral shrubs, with their associated lepidopteran herbivores, which grow across a mosaic of low-resource serpentine and higher-resource nonserpentine soils. Prior work in this system has found that plant resistance varies with soil type in a manner consistent with resource availability theory (23). Our goal is to understand how natural variation in abiotic resources might shape network modularity, and to parse the mechanistic basis of such differences between evolutionary (fundamental) and ecological (realized) trophic characteristics of species.…”
Section: Significancementioning
confidence: 63%
“…Species were Ceanothus cuneatus (nonserpentine; hereafter, NS) and Ceanothus jepsonii (serpentine; hereafter, S) (Rhamnaceae); Arctostaphylos manzanita (NS) and Arctostaphylos viscida (S) (Ericaceae); Quercus berberidifolia (NS) and Quercus durata (S) (Fagaceae); and Adenostoma fasciculatum (NS, S) (Rosaceae). We chose these species because they are the dominant chaparral vegetation in the region (25,26) and span a diverse phylogenetic range, and because prior work in this system has documented greater antiherbivore resistance overall in serpentine shrubs (23). At the study site, focal plant species comprise similar proportions of the woody plant species (40% and 44%, respectively) and families (26% and 24%, respectively) present in each soil type (SI Appendix, Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…While positive relationships between growth and defense are being increasingly documented among populations within species (Hahn and Maron 2016), this may vary depending on the natural history of the species examined. For example, resource limitation may enforce stronger trade-offs for highly defended species from stressful habitats compared with species originating from less stressful habitats (Hahn and Maron 2016;Robinson and Strauss 2018). Chemically defended species like milkweeds (Woods et al 2012) and mints (Rokaya et al 2016) or slow-growing species like boreal trees (Stevens et al 2016) and sagebrush (Pratt and Mooney 2013) may be more likely to exhibit growth-defense trade-offs across populations than less defended fast-growing species.…”
Section: Generalizing Across Species and Gradientsmentioning
confidence: 99%
“…Similarly, among milkweed species, tropical species tend to be more chemically defended, whereas temperate species tend to be less defended but more clonal (Pellissier et al 2016). Information on the habitat in which a species evolved, therefore, seems critical for describing intraspecific growthdefense strategies (Rokaya et al 2016;Stevens et al 2016;Robinson and Strauss 2018) and, importantly, correlations among growth and defense may differ depending on the traits being compared.…”
Section: Generalizing Across Species and Gradientsmentioning
confidence: 99%
“…mystiata less commonly collected (Fig. ; Robinson and Strauss ). Interestingly, co‐ocurring A. manzanita plants, which lack sticky trichomes on their fruits, support dramatically lower abundances of Eupithecia: of 48 Eupithecia caterpillars collected in 2014 and 2015, 47 were collected from A. viscida (despite equal sampling across both manzanita species).…”
mentioning
confidence: 99%